Casa el paraíso. Desarrollo de tipología en vivienda rural, municipio de montañita departamento Caquetá, Colombia (2020)
Rural housing represents that place where life not only peasant but also large cities develop. We must ask ourselves, is the conservation of rural areas important? Is the development of rural housing important for productivity or self-sustainability? Since the beginning of humanity, important events have arisen in environments where not only a production is created that helps the exchange of regions but also enjoy a quality of life with extensive green areas and housing with services that the same ecosystem can provide. However, nowadays, rural life has been put aside by the growth of large cities, causing abandonment or social cohesion to take it as a lifestyle. That is why, in order to show its importance in our environment, a more detailed analysis is generated where a design is determined as a reference for many typological possibilities for rural housing, which is affordable without generating a greater ecological impact.